Efficiency of a novel thermosensitive enema in situ hydrogel carrying Periplaneta americana extracts for the treatment of ulcerative colitis - Ming Wu; Ming Wu; Hui Ding; Xiao Tang; Jiayi Chen; Meng Zhang; Ziqiong Yang; Qian Du; Qian Du; Jun Wang; Jun Wang (Frontiers Media S.A., 2023)
Objective: The aim of this study was to develop a thermosensitive in situ gel (TISG) as an effective rectal delivery platform for delivering Periplaneta americana extracts (PA) to alleviate ulcerative colitis (UC) and explore the underlying molecular mechanism.Materials and methods: Thermosensitive (poloxamer 407) and adhesive polymers (chondroitin sulfate modified carboxymethyl chitosan, CCMTS) were used to construct the in situ gel. CCMTS and aldehyde poloxamer 407 (P407-CHO) were synthesized and chemically cross-linked by Schiff base reaction to formulate thermosensitive in situ gel, which carried Periplaneta americana extracts (PA/CCMTS-P). The cytotoxicity and cellular uptake of CCMTS-P were investigated in lipopolysaccharide (LPS) -induced macrophages by CCK-8 assay. The anti-inflammatory effects of PA/CCMTS-P were studied in lipopolysaccharide-induced RAW264.7 cells and dextran sulfate sodium (DSS)-induced ulcerative colitis mouse models. In addition, the ability of PA/CCMTS-P to restore the intestinal mucosal barrier after rectal administration was evaluated by immunohistochemical analysis (IHC).Results: PA/CCMTS-P was prepared and characterized as gel with a phase-transition temperature of 32.9°C. The results of the in vitro experiments indicated that the hydrogels promoted the cellular uptake of Periplaneta americana extracts without causing any toxicity as compared to the free gel. PA/CCMTS-P showed superior anti-inflammatory activity both in vitro and in vivo, which restored the damaged intestinal mucosal barrier associated by inhibiting necroptosis in dextran sulfate sodium-induced ulcerative colitis models.Conclusion: The findings from our study show that the rectal administration of PA/CCMTS-P holds a promising potential for the treatment of ulcerative colitis.